Roles of singlet oxygen and dissolved organic matter in self-sensitized photo-oxidation of antibiotic norfloxacin under sunlight irradiation - Niu, X.; Busetti, Francesco; Langsa, M.; Croué, Jean-Philippe (IWA Publishing, 2016)
Many fluoroquinolone (FLQ) antibiotics undergo rapid photodegradation in sunlit waters and form multifaceted photo-products. The high photodegradation rate is primarily ascribed to their photosensitizing properties. Though widely studied, the photo-reaction pathways are not completely revealed; photo-products mediated by different reactive oxygen species are not identified. In our study, photo-degradation of fluoroquinolone norfloxacin was investigated. A rapid degradation in buffered water was observed with a first-order rate constant of 2.45/hr and a quantum yield of 0.039. After light screening correction, selected DOMs (5 mg C/L) slightly enhanced the photodegradation rate with the exception of Suwannee river hydrophobic organic matter (SR-HPO). Three major photo-products were identified using high resolution mass spectrometry (HRMS). With 1O2 dark formation and competitor experiments, norfloxacin self-sensitized 1O2 was found to oxidize norfloxacin by inducing its piperazine chain cleavage. DOMs exhibited a dual role by inhibiting the 1O2-mediated reaction while enhancing the heterolytic defluorination pathway. DOMs were proposed to enhance heterolytic defluorination by donating electron to triplet state FLQ, this proposal was supported with specific UV absorbance (SUVA) as an indicator for the abundance of p bonds. Fluoride formation indicated a 79% elimination ratio of fluorine, an important functional group for antimicrobial activity. This work provides important new insights into the photochemical fate of fluoroquinolone antibiotics in natural water.